2020
DOI: 10.1016/j.transci.2020.102926
|View full text |Cite
|
Sign up to set email alerts
|

Anemia is associated with severe coronavirus disease 2019 (COVID-19) infection

Abstract: Letter to the Editor Anemia is associated with severe coronavirus disease 2019 (COVID-19) infectionDear Editor, Until recently, the number of positive and death cases from coronavirus disease 2019 (COVID-19) is still increasing. This pandemic disease has caused a significant impact and burden on all aspects of life, especially on the economic and health aspect. Therefore, identification of risk factors that contribute to the development of the severe disease is very important to enable risk stratification, opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 9 publications
7
66
0
2
Order By: Relevance
“…Both anemia and hypoalbuminemia have been associated with increased in-hospital mortality in other populations. [16][17][18][19] The higher rate of AKI in GN patients than in controls may have contributed to the increased mortality. Based on a recent meta-analysis of greater than 13,000 COVID-19 patients, the prevalence of AKI is 17%, 20 though there is considerable heterogeneity (0.5% to 80.3%) across different populations.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both anemia and hypoalbuminemia have been associated with increased in-hospital mortality in other populations. [16][17][18][19] The higher rate of AKI in GN patients than in controls may have contributed to the increased mortality. Based on a recent meta-analysis of greater than 13,000 COVID-19 patients, the prevalence of AKI is 17%, 20 though there is considerable heterogeneity (0.5% to 80.3%) across different populations.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
“…Both anemia and hypoalbuminemia have been associated with increased in-hospital mortality in other populations. 15 , 16 , 17 , 18…”
Section: Discussionmentioning
confidence: 99%
“…And TCM treatment significantly ameliorated the immune ability against SARS-CoV-2 in patients via reversing the levels of these indices 25 . Anemia was proved to be associated with severe COVID-19) infection 26 , and decreased HGB is common in forms of anemia. MCHC is lower in small cell anemia.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Previously published meta-analysis studies have identified several comorbidities that were associated with severe outcomes from COVID-19, such as obesity, hypertension, diabetes, thyroid disease, dyslipidemia, cardiovascular disease, and pulmonary disease. [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] Among patients with obesity, one of the most prevalent co-existing comorbid conditions was obstructive sleep apnea (OSA). OSA is the most common sleep-related breathing disorder and is highly prevalent, possibly affecting up to 1 billion people around the world.…”
Section: Introductionmentioning
confidence: 99%